Immediate Implant Placement in Aesthetic Zone: Crafting Smile with an Innovative Approach - Bista, Soni; Baniya, Bikash Kumar (Journal of Universal College of Medical Sciences, 2022)
Immediate implant placement is most commonly indicated when tooth extraction is performed owing to pathologies such as unrestorable caries or fractures. The primary advantage of this treatment modality is the diminution of healing time and reduced alveolar process resorption. Regenerative materials can be used as an adjunct with implants in order to triumph high implant survival rate and enrich good esthetic outcome. This case report illustrates treatment protocol and one-year clinical follow-up of a patient who underwent atraumatic extraction of his fractured mandibular central incisor, followed by immediate implant placement with bone grafts.